2003
DOI: 10.1002/per.482
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cross‐cultural invariance of the big five personality dimensions in work settings

Abstract: This article explores the cross-cultural invariance (construct validity) of two work-related personality inventories based upon the Five Factor Model (the HPI and the IP/5F). The results show a good convergent and discriminant validity between scales that measure the Big Five personality dimensions. A factor analysis indicates that all personality scales load on the hypothesized Big Five dimensions. Some implications of these findings for the research and practice of personality measurement in personnel select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
3
17
0
1
Order By: Relevance
“…These findings are consistent with much of the research on factor structure stability (Collins & Gleaves, 1998;Ellingson, Smith, & Sackett, 2001;Marshall et al (2005); Montag & Levin, 1994;Paulhus, Bruce, & Trapnell, 1995;Salgado, Moscoso, & Lado, 2003;Smith & Ellingson, 2002;Smith, Hanges, & Dickson, 2001;Tsaousis & Nikolaou, 2001). Depending on the fit index, the five-factor solution was an adequate to good fit for each inventory in both conditions.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with much of the research on factor structure stability (Collins & Gleaves, 1998;Ellingson, Smith, & Sackett, 2001;Marshall et al (2005); Montag & Levin, 1994;Paulhus, Bruce, & Trapnell, 1995;Salgado, Moscoso, & Lado, 2003;Smith & Ellingson, 2002;Smith, Hanges, & Dickson, 2001;Tsaousis & Nikolaou, 2001). Depending on the fit index, the five-factor solution was an adequate to good fit for each inventory in both conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Examining the content of the items for femininity and masculinity, it can be seen that the former suggests an agreeable, cooperative, and supportive style, while the latter suggests a rough, rude, competitive, and antagonistic style. The content of these items are also typically associated with the two poles of the agreeableness dimension in the Big Five Model of personality (Goldberg, 1992;Salgado, Moscoso, & Lado, 2003). It has been found that people who score higher in agreeableness also show more prosocial and helping behaviours, more citizen organizational behaviours and more contextual performance behaviours (Borman, et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the EPI and the IP/5F were.46 and.54 for emotional stability and extraversion, respectively ( N = 173). In another study ( N = 200), the correlations between the HPI and the IP/5F (Salgado, Moscoso, & Lado, ) were.75 for emotional stability,.69 and.74 for extroversion (HPI divides extroversion into two subfactors),.85 for openness,.51 for agreeableness, and.67 for conscientiousness. Therefore, it showed excellent convergence with other personality inventories assessing the same personality dimensions.…”
Section: Methodsmentioning
confidence: 95%